Pelatihan Transformasi Digitalisasi Menuju Koperasi Modern Dinas Perindustrian, Perdagangan dan Koperasi dan UKM Provinsi DKI Jakarta - Wahyudin, Wahyudin (LPPM Universitas Koperasi Indonesia, 2024)
The changing times are a necessity, and cooperatives, both as business institutions/companies and as social institutions, cannot avoid these changes. The information and internet era encourages all business entities to adapt to developments through digitalization. Digitization of cooperatives will lead to cooperatives that are efficient, fast, accurate and integrated between units, as well as collaboration with other cooperatives and the business world outside the cooperative will be easier. There are many advantages and benefits to cooperatives by digitalizing cooperatives. Especially nowadays, where many are dominated by Gen Z, who are very close to the world of the internet, data and convenience. Cooperative digitalization will attract them to become members of cooperatives and make transactions in cooperative companies